Sareomycetes: more diverse than meets the eye - James K. Mitchell; Isaac Garrido-Benavent; Luis Quijada; Donald H. Pfister (IMA Fungus)
Abstract Since its resurrection, the resinicolous discomycete genus Sarea has been accepted as containing two species, one with black apothecia and pycnidia, and one with orange. We investigate this hypothesis using three ribosomal (nuITS, nuLSU, mtSSU) regions from and morphological examination of 70 specimens collected primarily in Europe and North America. The results of our analyses support separation of the traditional Sarea difformis s.lat. and Sarea resinae s.lat. into two distinct genera, Sarea and Zythia. Sarea as circumscribed is shown to conservatively comprise three phylospecies, with one corresponding to Sarea difformis s.str. and two, morphologically indistinguishable, corresponding to the newly combined Sarea coeloplata. Zythia is provisionally maintained as monotypic, containing only a genetically and morphologically variable Z. resinae. The new genus Atrozythia is erected for the new species A. klamathica. Arthrographis lignicola is placed in this genus on molecular grounds, expanding the concept of Sareomycetes by inclusion of a previously unknown type of asexual morph. Dating analyses using additional marker regions indicate the emergence of the Sareomycetes was roughly concurrent with the diversification of the genus Pinus, suggesting that this group of fungi emerged to exploit the newly-available resinous ecological niche supplied by Pinus or another, extinct group of conifers. Our phylogeographic studies also permitted us to study the introductions of these fungi to areas where they are not native, including Antarctica, Cape Verde, and New Zealand and are consistent with historical hypotheses of introduction.